The interjection found in FIFA world cup - Eki Saputra (Universitas Muhammadiyah Enrekang, 2022)
This research has purpose to find out the interjections , clarify their meanings and describe their functions. The method of this research is descriptive qualitative study . In this research, it is described the meaning and the function of interjections used by the Commentator of FIFA World Cup 2014 match at group D The researcher conclude that there were 22 interjections that found in FIFA World Cup match commentator at group D, they were och, oh, wow, what, welcome, good evening, see you next time and etc. Those interjections are used to express some emotions like pity, surprise, sorrow, pain, wonder, greeting and farewell